Notes on well-being, motivation and job satisfaction of the college professor. - Fukuhara, Mary (2022)
The current conditions in which the college professor has to perform are different from the conditions they had before the COVID 19 pandemic, this new scenario could bring changes in their well-being, motivation and job satisfaction that would affect their performance. The purpose of this article is to present some notes on well-being, motivation and job satisfaction of college professor that invite reflection on these aspects and possible alternatives for improvements that allow them to teach in adequate conditions so that they achieve their maximum potential.